2021
DOI: 10.1093/braincomms/fcab051
|View full text |Cite
|
Sign up to set email alerts
|

Global decrease in brain sodium concentration after mild traumatic brain injury

Abstract: The pathological cascade of tissue damage in mild traumatic brain injury is set forth by a perturbation in ionic homeostasis. However, whether this class of injury can be detected in vivo and serve as a surrogate marker of clinical outcome is unknown. We employ sodium MRI to test the hypotheses that regional and global total sodium concentrations: (i) are higher in patients than in controls; and (ii) correlate with clinical presentation and neuropsychological function. Given the novelty of sodium imaging in tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 75 publications
2
8
0
Order By: Relevance
“…As the integrated 23 Na 32-channel receive phased-array of the dual-tuned 23 Na/ 1 H head coil prohibits the use of external references due to restricted space around the head, an internal reference had to be used. Besides the vitreous humor in the eyes, 22 CSF can be used as an internal reference for concentration calibration. 21 The determined sodium concentrations are in good agreement with the literature.…”
Section: Csf As An Internal Reference For Concentration Normalizationmentioning
confidence: 99%
See 1 more Smart Citation
“…As the integrated 23 Na 32-channel receive phased-array of the dual-tuned 23 Na/ 1 H head coil prohibits the use of external references due to restricted space around the head, an internal reference had to be used. Besides the vitreous humor in the eyes, 22 CSF can be used as an internal reference for concentration calibration. 21 The determined sodium concentrations are in good agreement with the literature.…”
Section: Csf As An Internal Reference For Concentration Normalizationmentioning
confidence: 99%
“…Regarding the signal calibration for quantification, external references with known 23 Na concentrations are mostly used. 18 As dedicated head coils with integrated receive phased arrays to enable improved spatial resolution by increasing SNR 19,20 often prohibit external references due to restricted space, using internal references such as the cerebrospinal fluid (CSF) 21 or vitreous humor 22 for quantification would be desirable. However, currently, these are rarely employed and further validation is necessary.…”
Section: Introductionmentioning
confidence: 99%
“…( Camici et al, 2006 ). reported that DMSO also can block Na + channel activation The Na + channel is activated by the physical impact on the brain tissue in TBI which leads to initiation of action potential and loss of membrane permeability culminating in necrosis and free radical generation ( Huang et al, 2014 ; Gerhalter et al, 2021 ). ( Jacob and Torre, 2009 ) reported a reduction in intracranial pressure, tissue edema, and inflammatory reactions by DMSO following TBI and these could further support its neuroprotective effects.…”
Section: Discussionmentioning
confidence: 99%
“…The Cohen’s d statistic, defined as the difference between mean metabolite levels divided by the pooled SD, was calculated as a measure of effect size for the differences between patients and controls: where , , , , , and , denote the patients’ (“p”) and controls (“c”) sample sizes, metabolite level means and SDs, following Davitz et al (2019) . A “small” effect was defined as | d | ≤ 0.5, a “medium” effect was defined as 0.5 < | d | < 0.8, and a “large” effect was defined as | d | ≥ 0.8, as done in Gerhalter et al, 2021 .…”
Section: Methodsmentioning
confidence: 99%